The effect of ERP implementation CSFs on business performance: an empirical study on users' perception - YURTKORU, EMİNE SERRA; AĞAOĞLU, MUSTAFA (ELSEVIER SCIENCE BV, 2015)
This study is conducted on 220 employees involved in ERP implementation project in a multinational consumer goods company to investigate the CSFs and their effect on ERP implementation success from users' point of view. Findings indicate there are differences in which CSFs are perceived important and actually have effect on ERP implementation success. Interestingly, none of the ERP adopting organization environment CSFs had influence on project success. Nevertheless, 'careful selection of ERP software', 'software analysis, testing and troubleshooting', and 'vendor support' explain ERP project outcomes.
Keywords: Business process outcomes; Critical success factors (CSFs); Enterprise resource planning (ERP); ERP project outcome; CRITICAL SUCCESS FACTORS; PROCESS OUTCOMES; SYSTEMS; TAXONOMY